Study progress on the pipeline transportation safety of hydrogen-blended natural gas - Tian, Xiao; Pei, Jingjing (Heliyon, 2023)
The core of carbon neutrality is the energy structure adjustment and economic structure transformation. Hydrogen energy, as a kind of clean energy with great potential, has provided important support for the implementation of the carbon peaking and carbon neutrality goals of China. How to achieve the large-range, safe, and reliable transportation of hydrogen energy with good economic benefits remains the key to limiting the development of hydrogen energy. Using the existing natural gas pipeline network can save many infrastructure construction costs to transport hydrogen-blended natural gas. However, due to great differences in the physical and chemical properties of hydrogen and natural gas, the transportation of hydrogen-blended natural gas will bring safety risks to the pipeline network operation to a certain extent. In this paper, the influences of pipeline transportation of hydrogen-blended natural gas on existing pipelines and parts along the pipelines are analyzed from two aspects of pipe compatibility and hydrogen blending ratio, and the safety of pipeline transportation of hydrogen-blended natural gas is summarized from two aspects of leakage and accumulation as well as combustion and explosion. In addition, the integrity management of hydrogen-blended natural gas pipelines and the existing relevant standards and specifications are reviewed. This paper points out the shortcomings of current hydrogen-blended natural gas pipeline transportation and gives some relevant suggestions. Hopefully, this work can provide a useful reference for developing a hydrogen-blended natural gas pipeline transportation system.